Use of Sexed Semen in Indian Dairy Cattle: A Case Study - Patel , S.B.; Jethva, P.C. (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
This study was undertaken at the calf rearing project (CRP) of AMUL at Sarsa Village, Anand, Gujarat to assess the conception rate and sorting efficiency of imported sexed semen of HF bulls. In all, 127 pubertal crossbred heifers (b.wt. 250-300 kg) were artificially inseminated during the year 2016-17 using 172 sexed semen doses (few with repeat insemination), resulting in 68 pregnancies. The conception rate of sexed semen was found to be 39.53%. Out of 68 pregnant heifers, 2 heifers aborted and one heifer died before calving. Out of rest 65 animals that calved, 54 heifers delivered female calves, 9 had male calves and two were female stillbirth. Thus, sexed semen produced 86.15% female calves and 13.85 % male calves. This small scale study highlights the success of sexed semen under field condition in producing calves of the desired sex in high percentage.
Keywords: Sexed semen; Stillbirth; Calf rearing; Conception rate; Sex ratio of calves